Understanding Individual Differences in the Dimensions of 'Vestedness' within Midwestern Populations toward the Novel Coronavirus (COVID-19) during Early-Stage Pandemic Onset. - MASON, A. M.; COMPTON, JOSH; SPENCER, ELIZABETH A. (Midwest Quarterly)
The article focuses on understanding individual differences in attitudes toward the novel coronavirus (COVID-19) in Midwestern populations during the early stages of the pandemic. Topics include the impact of emerging infectious diseases, the use of the extended parallel processing model in health communication scholarship, and an exploration of vestedness or stake in attitudes toward COVID-19 in the U.S. Midwest.